1992
DOI: 10.1254/jjp.58.259
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Halothane and Barbiturate Anesthesia in the Influence of Cerebral Ischemia on the Vagal Baroreflex in Dogs.

Abstract: ABSTRACT-In halothane-anesthetized dogs, a decrease in baroreflex sensitivity (BRS) of approximately 20% was observed during the reperfusion period following 5 min global cerebral ischemia. When compared with our previous study on animals under pentobarbital anesthesia, the extent of the decrease in BRS was smaller and apparently more severe ischemia was necessary to damage the vagal component of the baroreflex. Substitution of halothane with pentobarbital during the reperfusion period failed to affect either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…Figure 2 shows the correlation between the severity of ischemia and the extent of damage of the vagal com ponent of BRS. The correlation in the animals that were treated with halothane (open circles) was similar to that in the animals subjected to ischemia under halothane anesthesia in the previous study (4), where the correlation curve (dotted line H in Fig. 2) indicated that the vagal component of BRS survived an ischemic insult, if the mean residual blood flow during ischemia was greater than approximately 30%.…”
Section: Fig 1 Influence Of 5-min Global Cerebral Ischemia On Barorsupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 2 shows the correlation between the severity of ischemia and the extent of damage of the vagal com ponent of BRS. The correlation in the animals that were treated with halothane (open circles) was similar to that in the animals subjected to ischemia under halothane anesthesia in the previous study (4), where the correlation curve (dotted line H in Fig. 2) indicated that the vagal component of BRS survived an ischemic insult, if the mean residual blood flow during ischemia was greater than approximately 30%.…”
Section: Fig 1 Influence Of 5-min Global Cerebral Ischemia On Barorsupporting
confidence: 78%
“…Admin istration of halothane or thiopental increased the depth of anesthesia, producing an intermittent burst suppression of the cortical EEG in 5 out of 8 or 4 out of 6 animals, respectively, and reducing a (8 to 12.5 Hz) and ,8 (13 to 32 Hz) components of the EEG in the rest of the animals. Since our previous study (4) indi cated that a period of 60 to 120 min was necessary for the recovery from anesthesia with thiopental (10 mg/kg, i.v. ), BRS was measured during the period la ter than 120 min of reperfusion in animals pretreated with thiopental to avoid any direct effect of the addi tional anesthesia on BRS measurement.…”
mentioning
confidence: 99%